An improved model for heavy gas dispersion using time-varying wind data: Mathematical basis, physical assumptions, and case studies. (July 2015) - Li, Yue; Chen, Dongsheng; Cheng, Shuiyuan; Xu, Tingting; Huang, Qing; Guo, Xiurui; Ma, Xin; Yang, Nan; Liu, Xiangxue
Abstract: This study developed an improved model for the dispersion of released toxic gases, SLABi, based on the widely used model SLAB. Two major improvements enhanced the model's ability to represent observations. First, SLAB was upgraded to account for temporal variation in wind vectors. Thus, real-time changes in meteorological conditions can be considered in dispersion forecasting. Second, a source term module was developed and embedded in SLABi to standardize the procedure of emission calculation. Both the standard SLAB model and the SLABi model were applied to a case study to evaluate the impact of time-varying winds on the dispersion of released gases. The results showed that meteorology has a significant influence on the dispersion of released gases. The SLABi model can provide decision makers with timely and accurate guidance, so as to minimize hazards to people and the environment. Highlights: A new model, called SLABi, was developed for the dispersion of released toxic gases. SLABi can reflect the real-time changes in wind vectors in dispersion forecasting. A source term module was developed and embedded in SLABi. SLABi is more applicable for predicting the consequences of toxic gas release. SLABi can provide decision makers with timely and accurate guidance.